Legalitas Mobil Auto Pilot Dalam Prespektif Hukum Transportasi di Indonesia - Rizal Ramadhani Nusi (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe auto pilot car is one of the latest innovations in the world of transportation thanks to technological advancements. With this system the driver no longer needs to control the vehicle as a whole because the control system has been taken by the system. In the operation of all vehicles or modes of transportation, they must comply and not violate the norms in UULLAJ. Including the auto pilot car, the car currently operating and being traded in Indonesia must meet the requirements in UULLAJ and related to the due diligence and type test as stipulated in the Ministry of Transportation Regulation. Is the existence of an auto pilot car on the highway while maintaining the safety of other road users or vice versa? How big is the government's effort in carrying out the mandate of the law to provide a sense of security, comfort for all road users ?. The results of this research show that there are still no regulations that are detailed in detail regarding auto pilot cars and to ensure the safety of road users the government's efforts have not yet appeared in addressing this issue.Keywords: Autopilot Cars; Transportation Law; Legality of Auto Pilot Cars; Government Act.AbstrakMobil auto pilot merupakan salah satu inovasi terbaru di dunia transportasi berkat kemajuan teknologi. Dengan sistem tersebut pengemudi tidak perlu lagi mengendalikan kendaraan secara keseluruhan karena sistem kendali sudah di ambil oleh sistem. Dalam pengoperasian seluruh kendaraan atau moda transportasi wajib sesuai dan tidak melanggar norma yang ada dalam UULLAJ. Termasuk dengan mobil auto pilot, mobil tersebut saat ini beroperasi dan diperjual belikan di Indonesia wajib memenuhi persyaratan yang ada dalam UULLAJ serta terkait uji kelayakan dan uji tipe sebagaimana diatur dalam permenhub. Apakah dengan adanya mobil auto pilot di jalan raya tetap menjaga kemanan pengguna jalan lain atau sebaliknya? Seberapa besar upaya pemerintah dalam menjalankan amanat undang-undangan untuk memberikan rasa aman,nyaman bagi seluruh pengguna jalan raya?. Hasil dari peneilitan ini menunjukan bahwa masih belum ditemukan peraturan yang mengatur secara rinci terkait mobil auto pilot dan untuk menjamin keamanan pengguna jalan raya upaya pemerintah masih belum Nampak dalam menyikapi isu ini.Kata Kunci: Mobil Auto Pilot; Hukum Transpotasi; Legalitas Mobil Auto Pilot; Upaya Pemerintah.